Laparoscopic Cerclage as a Treatment Option for Cervical Insufficiency - Bolla, D.; Raio, L.; Imboden, S.; Mueller, M. D. (Geburtshilfe und Frauenheilkunde, 2015)
Background: The traditional surgical treatment for cervical insufficiency is vaginal placement of a cervical cerclage. However, in a small number of cases a vaginal approach is not possible. A transabdominal approach can become an option for these patients. Laparoscopic cervical cerclage is associated with good pregnancy outcomes but comes at the cost of a higher risk of serious surgical complications. The aim of the present study was to evaluate intraoperative and long-term pregnancy outcomes after laparoscopic cervical cerclage, performed either as an interval procedure or during early pregnancy, using a new device with a blunt grasper and a flexible tip. Methods: All women who underwent laparoscopic cervical cerclage for cervical insufficiency in our institution using the Goldfinger® device (Ethicon Endo Surgery, Somerville, NJ, USA) between January 2008 and March 2014 were included in the study. Data were collected from the patientsʼ medical records and included complications during and after the above-described procedure. Results: Eighteen women were included in the study. Of these, six were pregnant at the time of laparoscopic cervical cerclage. Mean duration of surgery was 55 ± 10 minutes. No serious intraoperative or postoperative complications occurred. All patients were discharged at 2.6 ± 0.9 days after surgery. One pregnancy ended in a miscarriage at 12 weeks of gestation. All other pregnancies ended at term (> 37 weeks of gestation) with good perinatal and maternal outcomes. Summary: Performing a laparoscopic cervical cerclage using a blunt grasper device with a flexible tip does not increase intraoperative complications, particularly in early pregnancy. We believe that use of this device, which is characterized by increased maneuverability, could be an important option to avoid intraoperative complications if surgical access is limited due to the anatomical situation. However, because of the small sample size, further studies are needed to confirm our findings.
Keywords: laparoscopic cerclage; Goldfinger® device; prematurity; cervical insufficiency; cervical cerclage; transabdominal cerclage